2018
DOI: 10.2337/db17-1043
|View full text |Cite
|
Sign up to set email alerts
|

Urinary IgG4 and Smad1 Are Specific Biomarkers for Renal Structural and Functional Changes in Early Stages of Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN) is the major cause of end-stage kidney disease, but early biomarkers of DN risk are limited. Herein we examine urinary IgG4 and Smad1 as additional early DN biomarkers. We recruited 815 patients with type 2 diabetes; 554 patients fulfilled the criteria of an estimated glomerular filtration rate (eGFR) >60 mL/min and no macroalbuminuria at baseline, with follow-up for 5 years. Patients without macroalbuminuria were also recruited for renal biopsies. Urinary IgG4 and Smad1 were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
(44 reference statements)
1
10
0
Order By: Relevance
“…Our results suggest alterations in SMAD1 gene expression without reduction in GFR, data confirmed by Doi et al (2018), who speculated that the presence of SMAD1 in urine precedes the decline of GFR in diabetics 35…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results suggest alterations in SMAD1 gene expression without reduction in GFR, data confirmed by Doi et al (2018), who speculated that the presence of SMAD1 in urine precedes the decline of GFR in diabetics 35…”
Section: Discussionsupporting
confidence: 91%
“…Doi et al (2018) investigated the presence of this protein in the urine of patients with DM2 and reported that SMAD1 is directly associated with mesangial matrix expansion, a classic feature of DN. In addition, increased urinary levels of SMAD1 have been found to precede the decline of GFR and of macroalbuminuria 35. SMAD1 protein expression had already been identified as a marker of mesangial matrix expansion in rats in the early phase of DN 36.…”
Section: Discussionmentioning
confidence: 98%
“…In the past decade, a number of novel molecules have been tested. [14][15][16] Among these, glycogen synthase kinase 3 (GSK3) has emerged as an attractive candidate.…”
mentioning
confidence: 99%
“…STAR (steroidogenic acute regulatory protein) [153], IL1RN [154], AQP5 [155], EGR1 [156], SFTPD (surfactant protein D) [157], KLF10 [158], PODXL (podocalyxin like) [159], FOXN3 [160], IL6R [161], PBX1 [162], APOD (apolipoprotein D) [163], ACVR2B [164], CD34 [165], INSR (insulin receptor) [166], APOA5 [167], STAR (steroidogenic acute regulatory protein) [168], PDK4 [169], GLS (glutaminase) [170], FKBP5 [171], SLC6A15 [172], MT2A [173], SLC38A4 [174], AQP7 [175], ABHD15 [176], ABCA1 [177], ZNRF1 [178], PPP1R3B [179], MAOA (monoamine oxidase A) [180], UBE2E2 [181], RNASEK (ribonuclease K) [182], PREX1 [183], DGKG (diacylglycerol kinase gamma) [184], POSTN (periostin) [185], COMP (cartilage oligomeric matrix protein) [186], GAP43 [187], P2RY12 [188], SELL (selectin L) [189] and DLG2 [190] have been revealed to be associated with type 2 diabetes mellitus, but these genes might be novel target for T1DM. Expression of ERRFI1 [191], ALOX12 [192], SOCS5 [193], DDIT4 [194], DUSP4 [195], IL6ST [196], DUSP1 [197], SMAD1 [198], NCL (nucleolin) [199], METTL14 [200], FMOD (fibromodulin) [201], CYGB (cytoglobin) [202], UNC5A [203] and TAAR9 [204] are associated with prognosis in patients with diabetic nephropathy, but these genes might be novel target for T1DM. A previous study reported that FAP (fibroblast activation protein alpha) [205], EYA4 [206], BCL9 [207], IRF2BP2 [208], EGR3 [209], GADD45B [210], DMD (dystrophin) [211], LSR (lipolysis stimulated lipoprotein receptor) [212], DLL4 [213], SUN2 [214], SOS1 [215], PIK3CA [216], GAMT (guanidinoacetate N-methyltransferase) [217], RBM47 […”
Section: Discussionmentioning
confidence: 99%